Step-up Maneuver for Radix Control in Dorsal Preservation Rhinoplasty - Neves, José Carlos; Rijo-Cedeño, Jefferson; Filgueiras, Halana; Arancibia-Tagle, Diego (Facial Plastic Surgery, 2025)
Radix control remains a key concern in preservation rhinoplasty. Consistent techniques for managing this area are essential for optimal outcomes.This article presents the step-up maneuver, a novel technique for precise modulation of radix height while preserving structural integrity.Retrospective case series.A retrospective analysis of 245 consecutive primary preservation rhinoplasties using the step-up maneuver between 2022 and 2023 was conducted.The subdorsal Tetris flap was employed in 86.1% of cases, whereas the low strip approach was used in 13.9%. Intraoperative outcomes included: Radix maintained—91.0%; Radix projected—2.9%; Radix deprojected—6.1%.The step-up maneuver represents a significant advancement in preservation rhinoplasty, broadening its indications and reducing the risk of radix-related complications. These findings suggest that preservation rhinoplasty can be safely and effectively extended to a wider range of nasal anatomies, further refining surgical strategies and reducing revision rates.
Keywords: rhinoplasty; preservation; step-up